Treatment of acquired perforant dermatoses with allopurinol - Matsuura, Naomi Carrara; Pereira, Fernanda; Nakazato, Lissa; Copi, Luana Rocco Pereira (Medicina (Ribeirao Preto), 2022)
Perforating dermatoses are papulonodular cutaneous pathologies characterized by transepithelial extrusion of components of the extracellular matrix of the dermis, by inflammation or degeneration. When secondary, the systemic diseases are called Acquired Perforating Diseases. Our letter aims to report a case of acquired perforating dermatoses secondary to chronic renal dialysis. The treatment with Allopurinol proved to be effective in this case. Allopurinol would act as an antioxidant, reducing the inflammatory reaction in tissues and consequent damage to the collagen fibers.